Recombinant Promoter (MUASCsV8CP) Driven Totiviral Killer Protein 4 (KP4) Imparts Resistance Against Fungal Pathogens in Transgenic Tobacco - Deb, Debasish; Shrestha, Ankita; Maiti, Indu B.; Dey, Nrisingha (Frontiers in Plant Science, 2018)
Development of disease-resistant plant varieties achieved by engineering anti-microbial transgenes under the control of strong promoters can suffice the inhibition of pathogen growth and simultaneously ensure enhanced crop production. For evaluating the prospect of such strong promoters, we comprehensively characterized the full-length transcript promoter of Cassava Vein Mosaic Virus (CsVMV; -565 to +166) and identified CsVMV8 (-215 to +166) as the highest expressing fragment in both transient and transgenic assays. Further, we designed a new chimeric promoter ‘MUASCsV8CP’ through inter-molecular hybridization among the Upstream Activation Sequence (UAS) of Mirabilis Mosaic Virus (MMV; -297 to -38) and CsVMV8, as the core promoter (CP). The MUASCsV8CP was found to be ~2.2 and ~2.4 times stronger than the CsVMV8 and CaMV35S promoters respectively, while its activity was found to be equivalent to that of the CaMV35S2 promoter. Furthermore, we generated transgenic tobacco plants expressing the totiviral ‘Killer protein KP4’ (KP4) under the control of the MUASCsV8CP promoter. Recombinant KP4 was found to accumulate both in the cytoplasm and apoplast of plant cells. The agar-based killing zone assays revealed enhanced resistance of plant-derived KP4 against two deuteromycetous foliar pathogenic fungi viz. Alternaria alternata and Phoma exigua var. exigua. Also, transgenic plants expressing KP4 inhibited the growth progression of these fungi and conferred significant fungal resistance in detached-leaf and whole plant assays. Taken together, we establish the potential of engineering “in-built” fungal stress-tolerance in plants by expressing KP4 under a novel chimeric caulimoviral promoter in a transgenic approach.